Evaluating Young People's Ability to Sustain an Evidence-Based Social Accountability Approach to Improve Adolescent Sexual and Reproductive Health in Ntcheu, Malawi - Mgoli Mwale, Patience; Msiska, Thumbiko; Wako, Etobssie; Chinkhota, Kriss; Munthali, Tapiwa; Rodriguez, Mariela; Shato, Thembekile; Laterra, Anne; Sebert Kuhlmann, Anne (Frontiers in Reproductive Health, 2021)
The Community Score Card© (CSC), a social accountability approach, brings together community members, service providers, and local government officials to identify issues, prioritize, and plan actions to improve local health services. In addition, young people in Ntcheu, Malawi have been using the CSC approach to mobilize their communities to bring change across varying issues of importance to them. An earlier cluster randomized trial in Ntcheu showed the CSC effectively increased reproductive health behaviors, improved satisfaction with services, and enhanced the coverage and quality of services. Building upon this evidence of effectiveness, this study aims to evaluate if and how young people were able to sustain implementation of the CSC, and the improvements it brings, approximately 2.5 years after the randomized trial ended. As part of a larger evaluation of CSC sustainability in Ntcheu, we conducted 8 focus groups across 5 health catchment areas with 109 members of mixed-gender youth groups (58 females and 51 males, ages 14–29 years) who continued to engage with the CSC. Audio recordings were transcribed, translated into English, and coded in Dedoose using an a priori codebook augmented with emergent codes and a constant comparative approach. Although the 8 youth groups were still actively using the CSC, they had made some adaptations. While the CSC in Ntcheu initially focused on maternal health, young people adopted the approach for broader sexual and reproductive topics important to them such as child marriages and girls' education. To enable sustainability, young people trained each other in the CSC process; they also requested more formal facilitation training. Young people from Ntcheu recommended nationwide scale-up of the CSC. Young people organically adopted the CSC, which enabled them to highlight issues within their communities that were a priority to them. This diffusion among young people enabled them to elevate their voice and facilitate a process where they hold local government officials, village leaders, and services providers accountable for actions and the quality of healthcare services. Young people organized and sustained the CSC as a social accountability approach to improve adolescent sexual and reproductive health in their communities more than 2.5 years after the initial effectiveness trial ended.